Semantics, culture, and cognition : universal human concepts in culture-specific configurations. configurations. - Wierzbicka, Anna (Oxford Univ Press, 1992)
Not everything that can be said in one language can be said in another. The lexicons of different languages seem to suggest different conceptual universes. Investigating cultures from a universal, language-independent perspective, this book rejects analytical tools derived from the English language and Anglo culture and proposes instead a "natural semantic metalanguage" formulated in English words but based on lexical universals. The outcome of two and a half decades of research, the metalanguage is made up of universal semantic primitives in terms of which all meanings--including the most cul.